TriPer, an optical probe tuned to the endoplasmic reticulum tracks changes in luminal H(2)O(2) - Melo, Eduardo Pinho (BMC Biol, 2017)
BACKGROUND: The fate of hydrogen peroxide (H(2)O(2)) in the endoplasmic reticulum (ER) has been inferred indirectly from the activity of ER-localized thiol oxidases and peroxiredoxins, in vitro, and the consequences of their genetic manipulation, in vivo. Over the years hints have suggested that glutathione, puzzlingly abundant in the ER lumen, might have a role in reducing the heavy burden of H(2)O(2) produced by the luminal enzymatic machinery for disulfide bond formation. However, limitations in existing organelle-targeted H(2)O(2) probes have rendered them inert in the thiol-oxidizing ER, precluding experimental follow-up of glutathione’s role in ER H(2)O(2) metabolism. RESULTS: Here we report on the development of TriPer, a vital optical probe sensitive to changes in the concentration of H(2)O(2) in the thiol-oxidizing environment of the ER. Consistent with the hypothesized contribution of oxidative protein folding to H(2)O(2) production, ER-localized TriPer detected an increase in the luminal H(2)O(2) signal upon induction of pro-insulin (a disulfide-bonded protein of pancreatic β-cells), which was attenuated by the ectopic expression of catalase in the ER lumen. Interfering with glutathione production in the cytosol by buthionine sulfoximine (BSO) or enhancing its localized destruction by expression of the glutathione-degrading enzyme ChaC1 in the lumen of the ER further enhanced the luminal H(2)O(2) signal and eroded β-cell viability. CONCLUSIONS: A tri-cysteine system with a single peroxidatic thiol enables H(2)O(2) detection in oxidizing milieux such as that of the ER. Tracking ER H(2)O(2) in live pancreatic β-cells points to a role for glutathione in H(2)O(2) turnover. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12915-017-0367-5) contains supplementary material, which is available to authorized users.